The Spillover Effects of Short-Term Shocks of Exogenous Macroeconomic Determinants on Pension Funds: Modelling on a Sample of Croatia - Bašić, Luka (Oeconomica Jadertina, 2024)
The study examines the spillover effects of exogenous macroeconomic shocks on Croatia’s pension system, focusing exclusively on the short-run (up to one year). The study’s methodology is based on an alternative approach through structural VAR modeling and variance decomposition (shock variance determination) to assess the strength of short-run shocks. The results indicate heterogeneity and asymmetry in the effects of short-run shocks on contributor trends and the asset value of contributions in both mandatory and voluntary (open) pension funds. Accordingly, two key findings emerge from the results. First, there is a statistically significant correlation between the spillover effects of shocks in most independent variables on the dependent ones in the models, with a particular emphasis on interest rate shocks within restrictive monetary policy. A specific time cycle is generally required to deepen the negative gap caused by shocks, typically from the third month onwards, with each percentage point shock leading to delta changes ranging from -1.2 to +1.4 p.p. Second, the cycle of restrictive monetary policy through interest rate increases impacts the structure of contributors and the assets/contributions in mandatory and voluntary pension funds in a heterogeneous and asymmetric manner. In mandatory pension funds, the negative impact mainly affects assets, while in voluntary funds, the negative impact extends to both the user/contributor trends and the funds’ asset values. The increase in interest rates under restrictive monetary policy leads to a decline in the value of existing bonds in fund portfolios due to the inverse relationship between interest rates and bond prices, which, in the short-run, results in a decrease in the funds’ asset values. Over the long-run, this same monetary policy cycle is expected to yield higher returns on new bonds, stabilizing assets through portfolio diversification. Mandatory pension funds, within the framework of their investment strategies, show lower volatility in contributor trends but are more sensitive to changes in asset value. Open voluntary pension funds, with their more flexible investment strategies, exhibit greater sensitivity to shock-induced changes in interest rates and inflation.